A new genus and a new species of freshwater fish Balitoridae, Cypriniformes from the Dien Bien district, Lai Chau province, Vietnam - Hao, Nguyen Van; Duc, Nguyen Huu (Academia Journal of Biology, 2015)
A new genus and a new species of freshwater fish Balitoridae, Cypriniformes from the Dien Bien district, Lai Chau province, Vietnam